Late medieval models, prehispanic heritage: towards a stylistic intention in the visuality of Guaman Poma de Ayala - Michaud, Cécile Anne (2018)
This article addresses the issue of the presence of an artistic consciousness—and more specifically of a stylistic intention—in Guaman Poma de Ayala’s work. This dimension is explored through two axes: Guaman Poma’s relationship with late-medieval visual sources, on the one hand, and to pre-Hispanic ones, on the other. Based on his drawings in the Nueva corónica y buen gobierno (c.1615-16), as well as some specific watercolor illustrations in Fray Martín de Murúa’s Historia del origen y genealogía real de los reyes ingas del Piru (from 1596 until after 1600), it discusses why the Andean author and artist, though fully immersed in viceregal religious and cultural contexts, focused his attention not on contemporary European artistic models, such as the Mannerists, but rather on late-medieval ones. The article also reveals how certain formal characteristics of pre-Hispanic origin were to be used or abandoned. Thus, it seeks to show how Guaman Poma was able to transcend the process of formal appropriation, thus finding a visual language tailored to his historical and political ambitions.